SENTRA UMKM KULINER DI SURABAYA - Fatmawarni, Fatmawarni; Hadinata, Irwan Yudha (JURNAL TUGAS AKHIR MAHASISWA LANTING, 2024)
The city of Surabaya's economy is mainly supported by the trade sector. However, due to the rapid competition in modern trade, small business owners are struggling to compete. To address this issue, Puncak CBD (Central Business District) has been developed as a vertical residential and integrated business area in West Surabaya City. This development aims to comes the residential needs of the people and provide equivalent facilities to compete with foreign products, especially for culinary MSMEs (Micro, Small and Medium Enterprises). A Culinary MSME Center has been established as a long-term facility to support the continuity of life and provide trading space for culinary MSME players. The Puncak contextual integrated concept has been employed to create this center, which is able to open up space for all groups and increase opportunities for Culinary MSMEs. The Contextual Architecture method has been applied to the building exterior to achieve harmony with the Puncak CBD area, producing a balanced visual environment.